2021
DOI: 10.1093/heapro/daab142
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition integrated agricultural extension—a case study in Western Kenya

Abstract: Summary Integrating nutrition communication in agricultural intervention programs aimed at increased food availability and accessibility in resource-poor areas is crucial. To enhance the sustainability and scalability of nutrition communication, the present study piloted the approach of ‘nutrition integrated agricultural extension’ and tested nutrition-related outcomes with two types of nutrition messages (specific vs. sensitive) and two delivery channels (public sector vs. private sector). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Farmers often associate darkgreen leaf color with high nutrient content (Keding et al, 2021), a trait that was more valued by the female farmers in the present study. The relationship between the degree of greenness and nutrient content has been not studied.…”
Section: Serial Nomentioning
confidence: 62%
“…Farmers often associate darkgreen leaf color with high nutrient content (Keding et al, 2021), a trait that was more valued by the female farmers in the present study. The relationship between the degree of greenness and nutrient content has been not studied.…”
Section: Serial Nomentioning
confidence: 62%
“…The erosion of indigenous knowledge about local wild species has led to the misconception that commercialized produce is healthier than indigenous species (Moyo et al, 2024;Nikolić et al, 2023). For example, Keding et al (2022) found that some indigenous Turkana fruits have higher nutritional content than apples, yet local communities in the region perceive exotic fruits like apples as more nutritious. This emphasizes the need for increased nutrient analysis and community awareness programs highlighting the nutritional significance of indigenous species.…”
Section: Factors Affecting the Adoption Of Indigenous Plant Species I...mentioning
confidence: 99%
“…For example, Keding et al. (2022) found that some indigenous Turkana fruits have higher nutritional content than apples, yet local communities in the region perceive exotic fruits like apples as more nutritious. This emphasizes the need for increased nutrient analysis and community awareness programs highlighting the nutritional significance of indigenous species.…”
Section: Why Species Diversity Is Key For Food System Transformationmentioning
confidence: 99%
“…Agriculture NGOs are usually tasked with promoting sustainable agricultural practices, providing support to farmers, and enhancing food security (Shames, 2019). To achieve these objectives, agriculture NGOs must rely on effective team leadership to mobilize resources and ensure that groups work together cohesively to achieve common goals (Keding, 2022). Agriculture projects are often complex, with multiple components that require coordination and collaboration among club members.…”
Section: Introductionmentioning
confidence: 99%